The Empire's Old Clothes : What the Lone Ranger, Babar, and Other Innocent Heroes Do to Our Minds - Dorfman, Ariel (Book collections on Project MUSE., 2010)
A classic text that challenges the ideologies behind much popular media, especially media aimed at children, which the Press will be putting back into print with a new preface.